2015
DOI: 10.1111/jre.12287
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival bacterial community profiles in HIV‐infected Brazilian adults with chronic periodontitis

Abstract: HIV-infected patients with chronic periodontitis present greater subgingival microbial diversity. In addition, the bacterial communities associated with HIV-infected and non-HIV-infected individuals are different in structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…Viral load 19 , CD4 counts 8,9,14 , periodontal status 7,8,20 , and smoking 21 have all been shown to be significant predictors of microbial composition in HIV-positive cohorts. If groups are not balanced, underlying differences among groups on these variables could easily obscure differences that result from HIV status, or lead to misattribution of differences that were not the result of HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…Viral load 19 , CD4 counts 8,9,14 , periodontal status 7,8,20 , and smoking 21 have all been shown to be significant predictors of microbial composition in HIV-positive cohorts. If groups are not balanced, underlying differences among groups on these variables could easily obscure differences that result from HIV status, or lead to misattribution of differences that were not the result of HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Moreover, an independent study revealed increased diversity in subgingival biofilms of HIV+ individuals within a Brazilian cohort of 32 subjects with PD. [20] …”
Section: Introductionmentioning
confidence: 99%
“…Ferreira et al (2016) have demonstrated that HIV-1-infected patients have significantly less visible supragingival plaque, as well as less periodontal inflammation and tissue destruction compared with non-HIV-1-infected patients [ 39 ]. The periodontal clinical parameters were also less severe in these HIV-infected patients than in non-HIV-1-infected patients, confirming previous data reported by other studies on the same population [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%